"I Don't Feel Like the Odd One": Utilizing Content Analysis to Compare the Effects of Social Media Use on Well-Being Among Sexual Minority and Nonminority US Young Adults. Issue 3 (March 2020) - Escobar-Viera, César; Shensa, Ariel; Hamm, Megan; Melcher, Eleanna M.; Rzewnicki, Daniel I.; Egan, James E.; Sidani, Jaime E.; Primack, Brian A.
Purpose: Although there is evidence of associations between social media (SM) use and mental well-being among the general population, these associations among lesbian, gay, and bisexual (LGB) persons are poorly understood. This study compared the influence of SM experiences on mental well-being between LGB and non-LGB persons. Design and Setting: Online cross-sectional survey. Participants: National sample of 2408 US adults aged 18 to 30 years. Method: We asked participants to provide examples of when SM affected their well-being separately in good and bad ways. We coded, summed, and used rate ratios (RRs) to compare responses of LGB and non-LGB individuals. Thematically similar codes were described and grouped into categories. Results: Most responses described positive SM effects. However, of 6 codes that were significantly more frequent among LGB respondents, only social capital (RR = 1.58, 95% confidence interval [CI], 1.17-2.12) described a positive effect. Five codes described negative effects of SM for LGB users: negative emotional contagion (RR = 1.28, 95% CI, 1.04-1.58), comparison with others (RR = 1.28, 95% CI, 1.01-1.62), real-life repercussions (RR = 1.86, 95% CI, 1.18-2.94), envy (RR = 2.49, 95% CI, 1.48-4.19), and need for profile management (RR = 2.32, 95% CI, 1.07-5.03). Conclusion: These findings suggest that, for LGB persons, gaining social capital from SM is valuable for establishing and maintaining connections. Increased negative SM experiences may pose a risk for the mental well-being of LGB individuals.